Tuberculosis Prevalence and Predictors Among Health Care-Seeking People Screened for Cough of Any Duration in Ethiopia: A Multicenter Cross-Sectional Study - Mohammed, Hussen; Oljira, Lemessa; Roba, Kedir Teji; Ngadaya, Esther; Manyazewal, Tsegahun; Ajeme, Tigest; Mnyambwa, Nicholaus P.; Fekadu, Abebaw; Yimer, Getnet (Frontiers in Public Health, 2022)
Background: Tuberculosis (TB) remains a major cause of morbidity and mortality in sub-Saharan Africa. This high burden is mainly attributed to low case detection and delayed diagnosis. We aimed to determine the prevalence and predictors of TB among health care-seeking people screened for cough of any duration in Ethiopia. Methods: In this multicenter cross-sectional study, we screened 241,052 outpatients for cough of any duration. We recruited a sample of 1853 presumptive TB (PTB) cases and categorized them into three groups: group I with cough > 2 weeks, group II with cough of < 2 weeks, and group III pregnant women, patients on antiretroviral therapy, and patients with diabetes. The first two groups underwent chest radiograph (CXR) followed by sputum Xpert MTB/RIF assay or smear microscopy. The third group was exempted from CXR but underwent sputum Xpert MTB/RIF assay or smear microscopy. TB prevalence was calculated across the groups and TB predictors were analyzed using modified Poisson regression to compute adjusted prevalence ratio (aPR) with a 95% confidence interval (CI). Results: The overall prevalence of PTB was 16.7% (309/1853). Of the positive cases 81.2% (251/309) were in group I (cough > 2 weeks), 44/309 (14.2% (44/309) in group II cough of < 2), and 4.5% (14/309) in group III (CXR exempted). PTB predictors were age group of 25-34 (aPR = 2.0 [95% CI 1.3-2.8]), history of weight loss (aPR = 1.2 [95% CI 1.1-1.3]), and TB suggestive CXRs (aPR = 41.1 [95% CI 23.2-72.8]). Conclusion: The prevalence of confirmed PTB among routine outpatients was high, and this included those with a low duration of cough who can serve as a source of infection. Screening all patients at outpatient departments who passively report any cough irrespective of duration is important to increase TB case finding and reduce TB transmission and mortality.